The Early Application of Electrophoresis of Protein in Higher Plant Taxonomy - SURANTO SURANTO (Society for Indonesian Biodiversity, 2002)
The aims of this research are firstly, to study the advantages of electrophoretic techniques. Secondly, to look at the usefulness of a few mediums support of electrophoretic proteins especially the acrylamide gel. Thirdly, to examine thenumber of plant organs which could be used as the sources of plant proteins, and how these plants protein should be applied in the medium support that has been selected. Besides, the staining and detection procedures would be described, while the application of electrophoretic approach in higher plant taxonomy will also be evaluated. In this study we recorded that a number of taxonomic problems usually caused by morphological complexity within species can be solved using this experimental approach of electrophoresis. This method has been considered very useful in helping taxonomists making decisions.ïƒ£ 2002 Jurusan Biologi FMIPA UNS SurakartaKey words: electrophoresis, proteins, taxonomy